Exploring Discretionary HR Practices and Human Resource Service Orientation on Employee Motivation and Performance at PT RAF: A Qualitative Study Based on Regulatory Focus Theory - Rafyanti Widyarini; Sitti Rakhman (Paspama Institute, 2025)
This study explores how discretionary human resource (HR) practices and HR service orientation influence employee motivation and performance at PT RAF, a general insurance company in Indonesia. Employing a purely qualitative approach through non-participant observation and in-depth interviews with employees and HR representatives, the findings reveal that HR practices at PT RAF remain largely administrative, with limited attention to career development, training, and employee involvement. A low HR service orientation further weakens the effectiveness of HR policies. Consequently, most employees exhibit a prevention-focused motivational pattern, prioritizing error avoidance over achievement. These findings highlight the need for HR transformation toward a more strategic and service-oriented role to foster promotion-focused motivation and enhance overall employee performance.